Scientific Production of Behavioral Movement on Peruvian Indexed Journals: A Bibliointegrated Study - Richard Jhunior Mejia-Velarde; Giuliana Salazar-Alvarez (Interacciones)
The permanent development of behavioral psychology as an alternative to the scientific study of behavior and its contributions from Latin America motivated the present investigation with the objective of describing the scientific production of the behavioral movement in Peru during the 21st century. The bibliointegrative method was used, through a list of hemerographic attributes that characterize the research at a generic, thematic, methodological, sampling and documentary levels. It was analyzed 110 articles published between 2000 and 2017 in Peruvian indexed journals, selecting original theoretical and empirical research with a theoretical-behavioral foundation. The results are presented by descriptive statistics. It found that cognitive behavioral dominance in empirical and technological research, and interbehavioral and skinnerian in theoretical research. The designs most used were non-experimental of simple correlational type, was using descriptive and inferential statistics for hypothesis testing. The studies were conducted only in humans, in different age groups and primarily using non-probability sampling. The authors used primary sources, mostly from spanish and english origin and average age not exceeding 10 years. In conclusion, behavioral research shares characteristics of Peruvian research in general: limited number of publications, focusing on human and aimed at applicative contexts.